Platelet-derived growth factor (PDGF) in neoplastic and non-neoplastic cystic lesions of the central nervous system and in the cerebrospinal fluid. - Nistér, M. (Nature Publishing Group, 1994)
The aim of this study was to determine the concentration of PDGF in vivo in neoplastic and non-neoplastic brain lesions. Fluid from cystic lesions and cerebrospinal fluid was tested in a radioreceptor assay that detects all described PDGF isoforms. High concentration of PDGF were found in cyst fluids from several astrocytomas, one metastatic melanoma, one metastatic lung adenocarcinoma and one intracerebral abscess. The PDGF concentrations were several times higher than the levels known to be required for maximal PDGF effects on cells in vitro. PDGF could also be detected in some non-neoplastic lesions, especially one intracerebral abscess. The finding of high amounts of PDGF in neoplastic lesions strongly supports the possibility that PDGF can be a mediator of tumour and stromal cell growth and motility in vivo. Comparison of PDGF and beta-thromboglobulin concentrations in the same fluids strongly indicates that the PDGF protein is locally produced rather than a result of platelet activation and derangement of the blood-brain barrier.